Study of potassium oxalate based slurry for Copper/Cobalt CMP. (2022) - Kumar, Rohan; Hazarika, Jenasree; Venkatesh Rajaraman, Prasanna
Abstract: In a Chemical Mechanical Planarization (CMP) process, formulation of slurry that would give a desired selectivity and a reduced galvanic corrosion between the barrier metal (Co) and interconnect (Cu) has been a major concern in the semiconductor industry. The study presented here aims to find a suitable slurry composition in a fumed silica-based slurry with potassium oxalate (oxidizer), glycine (complexing agent) and benzotriazole (inhibitor) which would offer a Co/Cu selectivity as close as ∼ 1:1 along with minimizing the galvanic corrosion. The role of the different slurry components on removal rates and etch rates at different pH range were investigated. It was seen that in a 2 wt% fumed silica-based slurry, using 3 M potassium oxalate, 1 M glycine and 5 mM benzotriazole at pH 9 gave a desired Co/Cu selectivity of ∼ 1.2:1 along with low etch rates. Benzotriazole played the role of an inhibitor by reducing the galvanic corrosion to ∼ 60 mV from ∼ 140 mV on its addition at optimized pH 9.